(untitled) (Hoboken, N.J., 2006)
This work provides a collection of current research papers including valuable insights on materials-related aspects of solid-oxide fuel cells current status, processing and fabrication, various electrolytes, anodes, and cathodes, ceramic/metal interconnects, seal materials, mechanical properties, characterization, modeling, fuel reforming, component materials, materials processing, performance, stability, and more.
Keywords: Solid oxide fuel cells,Tế bào nhiên liệu oxit rắn